2019
DOI: 10.1159/000494734
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of SPARC Is Associated with Epithelial-Mesenchymal Transition and Low Differentiation State of Biliary Tract Cancer Cells

Abstract: Background: Biliary tract cancers (BTCs) have a poor prognosis. BTCs are characterized by a prominent desmoplastic reaction which possibly contributes to the aggressive phenotype of this tumor. The desmoplastic reaction includes excessive production and deposition of extracellular matrix proteins such as periostin, secreted protein acidic and rich in cysteine (SPARC), thrombospondin-1, as well as accumulation of α-smooth muscle actin-positive cancer-associated fibroblasts and immune cells, secreting growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have indicated that the expression of SPARC in gastric cancer is correlated with the expression of E-cadherin, Slug and Vimentin, and the positive expression of SPARC is negatively correlated with the survival rate of patients with gastric cancer. Positive expression of E-cadherin is positively correlated with the survival rate of patients with gastric cancer ( 7 ). At the same time, it has been indicated that SPARC may affect the metastasis of lung cancer through the Wnt/β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the expression of SPARC in gastric cancer is correlated with the expression of E-cadherin, Slug and Vimentin, and the positive expression of SPARC is negatively correlated with the survival rate of patients with gastric cancer. Positive expression of E-cadherin is positively correlated with the survival rate of patients with gastric cancer ( 7 ). At the same time, it has been indicated that SPARC may affect the metastasis of lung cancer through the Wnt/β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Deng et al confirmed that the SPARC content is increased in CCA tissues and cells, and SPARC elevated CCA cell proliferation, metastasis, and EMT [30]. In addition, a lack of SPARC was linked with EMT and low differentiation conditions in biliary tract cancer [31]. However, Hu et al showed that SPARC upregulation in M2-type macrophages can inhibit M2-mediated promotion of growth, migration and antiapoptotic effects in gastric cancer (GC).…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that SPARC expression can be induced remarkably with the development of lung, esophageal, pancreatic, and prostate cancer, suggesting that SPARC could be a tumor promoter[ 5 - 9 ]. In detail, mechanism studies revealed that SPARC regulated the tumor growth factor β (TGF-β) signaling and then promoted the epithelial-mesenchymal transition (EMT), which participates in the cancer metastasis[ 5 , 10 , 11 ]. SPARC was a tumor promoter to activate the phosphatidylinositol 3-phosphate kinase (PI3K)/AKT pro-oncogenic pathway[ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%